The Perfect Secret (A Jessie Hunt Psychological Suspense Thriller-Book Eleven) - Blake, Pierce (Lukeman Literary, 2020)
"A masterpiece of thriller and mystery. Blake Pierce did a magnificent job developing characters with a psychological side so well described that we feel inside their minds, follow their fears and cheer for their success. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) THE PERFECT SECRET is book #11 in a new psychological suspense series by bestselling author Blake Pierce, which begins with The Perfect Wife, a #1 bestseller (and free download) with over 500 five-star reviews. A wealthy mogul throws an exclusive party in his sprawling and secretive Beverly Hills mansion, only to have the night end with one of his high-society guests murdered-forcing Jessie to enter the sleazy world of the elite. As Jessie begins to unearth the secrets they hide behind their perfect facades, she wonders: was the murder related to an affair? Or was there a much more nefarious motive at stake? A fast-paced psychological suspense thriller with unforgettable characters and heart-pounding suspense, THE PERFECT SECRET is book #11 in a riveting new series that will leave you turning pages late into the night. Books #12-#15 are also available!
Keywords: Dobrodružství, napětí, thrillery; Krimi, detektivky